Diseño de una actividad integradora para la enseñanza del concepto de respiración humana en estudiantes de 7° grado de un colegio del Municipio de Soacha (Memorias Sifored - Encuentros Educación UAN, 2023)
This research addresses interdisciplinary teaching as an alternative that has been shown to be effective for the development of scientific skills, as it allows students to better understand natural phenomena (Busquets, Silva, & Larrosa, 2016). A summary of the general research is proposed, focused on showing the development of our integrative design, focused on the concept of human respiration and proposed for 6th and 7th grade students of a private educational institution in the municipality of Soacha. Initially, a diagnosis of scientific competencies was carried out through the application of the Saber 7 Test questionnaire, version 2021, in the area of ​​natural sciences. The results showed that of the three competencies evaluated: inquiry, explanation of phenomena and comprehensive use of scientific knowledge, the greatest difficulties were in the questions related to the explanation of phenomena. For the development of the integrative project, there was the collaboration of the teachers of the subjects of chemistry, biology and physical education. The integrative project called “Understanding Respiration” was proposed to be developed in 4 weeks, and addresses aspects such as the functions of the respiratory system, gas exchange and breathing control.
Keywords: Curriculum innovation; interdisciplinarity; didactics; natural science; scientific competence